2002
DOI: 10.1103/physrevb.65.201102
|View full text |Cite
|
Sign up to set email alerts
|

Light scattering from a monolayer of periodically arrayed dielectric spheres on dielectric substrates

Abstract: Theoretical studies have revealed that coupling with a dielectric substrate significantly affects the transmission spectrum of a 2D photonic crystal of monolayer dielectric spheres. The dielectric constant of a semiinfinite substrate has been found to have a threshold, above which dips in the transmission spectrum broaden drastically. A substrate of finite thickness yields additional dips in the spectrum corresponding to localized eigenstates within the substrate. The transmission spectrum is well explained by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
32
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 13 publications
(13 reference statements)
4
32
0
1
Order By: Relevance
“…The spectral position and resolution of scattering resonances depend on the RI of substrate. 14,16 In our case the RI of the substrate exceeds the effective RI of the sphere monolayer. In order to use the waveguiding model, we have to assume that a monolayer of spheres is optically isolated from the substrate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The spectral position and resolution of scattering resonances depend on the RI of substrate. 14,16 In our case the RI of the substrate exceeds the effective RI of the sphere monolayer. In order to use the waveguiding model, we have to assume that a monolayer of spheres is optically isolated from the substrate.…”
mentioning
confidence: 99%
“…Moreover, no spectroscopic evidence has been demonstrated to prove the formation of a 3D lattice in LB multilayers. 9 On the other hand, optical spectra of 2D hexagonal sphere crystals were studied only at wavelengths shorter than the sphere diameter, 10,11 i.e., in the range of their 2D PBG.…”
mentioning
confidence: 99%
“…Moreover, this theory predicts considerable broadening of the minima bandwidth due to light leakage to the substrate. 35 The spectral position of the first bandgap in such PhC corresponds to the sphere diameter and the next gap takes place at a wavelength, which is lower by a factor of 1.21. The observed minima at 548 and 444 nm for 1L LB film are in good agreement with this model.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the resonance enhances the intensity of a local field by two orders of magnitude if the monolayer of spheres is suspended in the air, whereas the attached substrate reduces the enhancement by factor of 10. 6,7,35 The distribution of the local field at the surface of the opal-based PhC in the PBG wavelength range was modeled theoretically 36 and visualized by the near-field optical microscopy. 9 Since the near-field amplitude of evanescent waves decays rapidly away from a PhC surface on a scale of the PhC lattice constant, the NCF-based emitter should be in close proximity to a PhC surface.…”
Section: Discussionmentioning
confidence: 99%
“…We chose the parameters of the multilayer in such a way that it has a broad stopband covering the range of normalized frequencies (ωa/2πc) from 0.5 to 1, because the guided mode resonances of the monolayer PhC at Γ-point will be in this range [9] as shown in the band diagram of the monolayer [see Fig. 6A in Appendix].…”
mentioning
confidence: 99%